Cross-phenotype association tests uncover genes mediating nutrient response in Drosophila. (December 2016) - Nelson, Christopher; Beck, Jennifer; Wilson, Kenneth; Pilcher, Elijah; Kapahi, Pankaj; Brem, Rachel
Abstract Background Obesity-related diseases are major contributors to morbidity and mortality in the developed world. Molecular diagnostics and targets of therapies to combat nutritional imbalance are urgently needed in the clinic. Invertebrate animals have been a cornerstone of basic research efforts to dissect the genetics of metabolism and nutrient response. We set out to use fruit flies reared on restricted and nutrient-rich diets to identify genes associated with starvation resistance, body mass and composition, in a survey of genetic variation across theDrosophila Genetic Reference Panel (DGRP). Results We measured starvation resistance, body weight and composition in DGRP lines on each of two diets and used several association mapping strategies to harness this panel of phenotypes for molecular insights. We tested DNA sequence variants for a relationship with single metabolic traits and with multiple traits at once, using a scheme for cross-phenotype association mapping; we focused our association tests on homologs of human disease genes and common polymorphisms; and we tested for gene-by-diet interactions. The results revealed gene and gene-by-diet associations between 17 variants and body mass, whole-body triglyceride and glucose content, or starvation resistance. Focused molecular experiments validated the role in body mass of an uncharacterized gene, CG43921 (which we renameheavyweight ), and previously unknown functions for the diacylglycerol kinaserdgA, the huntingtin homologhtt, and the ceramide synthaseschlank in nutrient-dependent body mass, starvation resistance, and lifespan. Conclusions Our findings implicate a wealth of gene candidates in fly metabolism and nutrient response, and ascribe novel functions tohtt, rdgA, hwt andschlank .